A STUDY OF THE CLINICAL UTILIZATION OF SURAL NERVE BIOPSY IN NEUROLOGICAL PRACTICE OVER A SEVEN YEAR PERIOD IN GREATER MANCHESTER. Issue 11 (9th October 2013) - Khan, Sidra; Srirathan, Vino; Gosal, David Yunus
Abstract : 90 patients were identified for study by accessing pathology records. The biopsies were performed for numerous clinical indications, the most common being: Suspected vasculitis: 31 patients. Suspected inflammatory neuropathy (Chronic Inflammatory Demyelinating Polyneuropathy/Dorsal Root Ganglionopathy) [sensory ataxic state and equivocal Nerve Conduction Studies]: 21 patients. Results: In total in 32 patients, the biopsy was deemed to have actively changed management e.g. confirmed the presence of suspected vasculitis, confirmed diagnosis of CIDP, or other inflammatory neuropathy. The nerve biopsy was non–contributory in only 7 cases. 42 patients also had an accompanying muscle biopsy, which was mainly utilised to aid in the diagnosis of vasculitic neuropathy. Of the individuals who had histopathological features supportive of peripheral nerve vasculitis, the accompanying muscle biopsy did not show vasculitic changes. In one case however vasculitic changes were observed in muscle and not in sural nerve. Interestingly, the expansion of the Neuromuscular Service over this period led to a paradoxical fall in annual biopsy rates. We suspect that this phenomenon could be expliained by more accurate electroclinical diagnosis negating the need for nerve biopsy in certain individuals. The associated complication rate was low: 2 patients reporting increased pain 5 delayed healing 2 infection Sural nerve tissue was retrieved in all cases Conclusions: 1. Sural nerve biopsy continues to play a useful but albeit limited role in the diagnosis of peripheral neuropathies, mainly limited to the diagnosis of vasculitis or more clinically challenging inflammatory neuropathy cases. 2. Although literature states that in almost 50% of cases with confirmed vasculitis, accompanying muscle biopsy also shows vasculitic change, we did not observe this and question its utility. 3. Complication rates from the procedure are low.